1991
DOI: 10.1152/ajpcell.1991.260.5.c1039
|View full text |Cite
|
Sign up to set email alerts
|

Humoral factors reduce gap junction sensitivity to cytoplasmic pH. II. In vitro manipulations

Abstract: Our previous studies demonstrated a diurnal rhythm in the response of gap junctions between crayfish giant axons to acidification and that the response was reduced after eyestalk ablation, sinus gland removal, or visual stress. In this paper we describe experiments to test whether compounds in the circulating hemolymph were responsible for modulation of the responsiveness gap junction channels to intracellular pH. In axons from destalked animals in which the hemolymph had been replaced with normal saline, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Examples of these latter processes include increased intracellular Ca 2+ , which is known to inhibit electrical coupling (Connors and Long 2004), or activation of other modulatory neurons in the leech brain as a result of AMPA application. Previous work has shown that serotonin inhibits electrical synapses in the leech CNS (Colombaioni and Brunelli 1988;Beck et al 2002;Moss et al 2005) and neuronal gap junctions have been shown to be modified by a variety modulatory transmitters or hormones including serotonin, ecdysone, dopamine and acetylcholine (Piccolino et al 1984;Teranishi et al 1983;Moreno et al 1991;Johnson et al 1993Johnson et al , 1994Rorig and Sutor 1996;Velazquez et al 1997;Teshiba et al 2001;Antonsen and Edwards 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these latter processes include increased intracellular Ca 2+ , which is known to inhibit electrical coupling (Connors and Long 2004), or activation of other modulatory neurons in the leech brain as a result of AMPA application. Previous work has shown that serotonin inhibits electrical synapses in the leech CNS (Colombaioni and Brunelli 1988;Beck et al 2002;Moss et al 2005) and neuronal gap junctions have been shown to be modified by a variety modulatory transmitters or hormones including serotonin, ecdysone, dopamine and acetylcholine (Piccolino et al 1984;Teranishi et al 1983;Moreno et al 1991;Johnson et al 1993Johnson et al , 1994Rorig and Sutor 1996;Velazquez et al 1997;Teshiba et al 2001;Antonsen and Edwards 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the lateral giant axons of the crayfish, the circulating hormone ecdysterone reduces gap junction sensitivity to changes in cytoplasmic pH (Moreno et al 1991). In the retina of both turtles and carp, dopamine narrows the receptive field profile of H1 horizontal cells by decreasing the conductance of gap junctions between axon terminals through a cyclic AMP-dependent pathway (Piccolino et al 1984;Teranishi et al 1983).…”
Section: Serotonergic Modulation Of Electrical Coupling Between S Cellsmentioning
confidence: 99%
“…Subsequent in vitro studies using purified astrocytic cultures substantiated the prevalence of Cx43 in this class of macroglial cells (Dermietzel et al, 1991;Giaume et al, 1991). Because the particular type of channel-forming protein seems to determine the functional characteristic of the gap junction channels with respect to their voltage dependence (Harris et al, 1981;Spray et al, 1991), pH sensitivity (Campos de Carvalho et al, 1984;Spray and Bennett, 1985;Spray et al, 1986;Moreno et al, 1991a), potential for modulation by phosphorylation (Saez et al, 1986;Traub et al, 1987), unitary conductance (for review, see Spray and Saez, 1987), and dye transfer (Steinberg et al, 1994) the existence of different types of connexins among the glial cell populations may be of considerable functional significance.…”
Section: Introductionmentioning
confidence: 97%